MELACAK AKAR BIAS GENDER DALAM STUDI ISLAM - Maulana - (Marwah: Jurnal Perempuan, Agama dan Jender, 2016)
This paper will try to decipher some of the contemporary issues related to the root of the problem of gender bias in the study of Islam. Among the issues which form the basis of the emergence of gender bias in the study of Islam is the First, the issue of the creation of Eve in Sura al-Nisa verse 1. Second, the issue of leadership of women over men. Third, Woman and Sin Heritage. From this context, it can be understood that the teachings of Islam do not subscribe to the ideology that prohibits female lead, also bebrabai myth tentan creation of Eve. Because, it all would give a heavy burden on women. Like the myth of menstruating women as though he had not seen and treated as human beings, because in addition to be consigned should also perform various hard rituals.